Cleaved but not endogenous secretory RAGE is associated with outcome in acute ischemic stroke. (19th January 2016) - Tang, Sung-Chun; Yeh, Shin-Joe; Tsai, Li-Kai; Hu, Chaur-Jong; Lien, Li-Ming; Peng, Giia-Sheun; Yang, Wei-Shiung; Chiou, Hung-Yi; Jeng, Jiann-Shing
Abstract : Objective: To investigate the expression patterns of 2 soluble isoforms of receptor for advanced glycation end-product (RAGE), including endogenous secretory RAGE (esRAGE) and cleaved RAGE (cRAGE), and their associations with outcome in acute ischemic stroke (IS). Methods: Acute IS patients (n = 106) and age- and sex-matched controls (n = 150) were recruited. Plasma levels of total soluble RAGE (sRAGE) and esRAGE in patients at <48 hours and 48–72 hours after IS and in controls were measured by ELISA. The level of cRAGE was calculated by subtracting the level of sRAGE from that of esRAGE. Poor outcome was defined as modified Rankin Scale score >2 at 3 months after stroke. Results: The plasma levels of cRAGE were significantly higher and correlated to those of esRAGE ( p < 0.001). The plasma levels of esRAGE and cRAGE were both significantly higher in IS patients <48 hours and 48–72 hours after onset than in controls, but only level of cRAGE at <48 hours was independently associated with poor outcome after adjusting for clinical variables (odds ratio 2.44; 95% confidence interval 1.16–5.16; p = 0.019). Conclusion: The plasma level of cRAGE at <48 hours after IS, rather than esRAGE, is a significant predictor of acute IS outcome.